Correction: Severe Strongyloides stercoralis infection in kidney transplant recipients: A multicenter case-control study. - PLOS Neglected Tropical Diseases Staff (PLoS Neglected Tropical Diseases)
[This corrects the article DOI: 10.1371/journal.pntd.0007998.].